THE DEVELOPMENT OF STUDENT CARE AND SUPPORT SYSTEM MANAGEMENT USING THE SOMDETPIT MODEL TO IMPROVE STUDENT QUALITY IN SOMDETPITTAYAKOM SCHOOL - Saenkanya, Phumsak (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The main objective of the research article was to study and develop a model of student care and support system management using the SOMDETPIT Model to improve student quality in Somdetpittayakom School. The sub-objectives were 1) to study the current situation and problems of student care and support system management, 2) to develop the model of student care and support system management using the SOMDETPIT Model, 3) to study the model implementation and 4) to evaluate the model. The design of this study was Research and Development (R&D). Phase 1 was a study concerning current situation and problems of student care and support system management by using documentary analysis and stakeholder interviews. Phase 2 was a design and inspection of the SOMDETPIT model using focus group discussion. Phase 3 was the model implementation. The target group consisted of teachers, students, and board of basic education institution during academic year 2020 to 2021. Phase 4 was a performance evaluation and model improvement. The research results revealed that; 1. Regarding the current situation and problems of student care and support system management, the overall operation was accomplished; however, information system, student screening, teachers support in student care and support system should be improved. 2. The development process of the student care and support system management consisted of planning, doing, checking, acting and improving. There were 9 elements of SOMDETPIT model indicating desirable characteristics or student quality. 3. To study the model implementation is divided into 2 issues. Issue 1 was a study in systematic model and appropriateness of school contexts. Issue 2 was the SOMDETPIT model implementation. 4) An evaluation of student care and support system management using the SOMDETPIT model was at the high level.